Labour developments, living standards and well-being in Eastern Europe before the transition - Vasily Astrov; Branimir Jovanović (The Vienna Institute for International Economic Studies (wiiw), 2024)
This article examines trends in population, labour, prices, incomes and consumption across eight Eastern European countries - Bulgaria, Czechoslovakia, East Germany, Hungary, Poland, Romania, the Soviet Union and Yugoslavia - between 1950 and 1990. It finds that, despite persistent shortages, economic and social conditions generally improved until the late 1970s. Incomes and consumption rose steadily, and access to education and health care expanded, often at rates comparable to or even surpassing those in some Western European economies. However, the 1980s brought mounting economic challenges, as the state increasingly lost labour to the informal sector, wages and incomes stagnated, inflation surged in several countries, and consumption growth began to slow significantly.
Keywords: N34; P22; P23; P24; 330; population; labour; incomes; prices; consumption; living standards; well-being; Eastern Europe; socialism